Vertical Transmission of a Drosophila Endosymbiont Via Cooption of the Yolk Transport and Internalization Machinery - Herren, Jeremy K. (American Society of Microbiology, 2013)
Spiroplasma is a diverse bacterial clade that includes many vertically transmitted insect endosymbionts, including Spiroplasma poulsonii, a natural endosymbiont of Drosophila melanogaster. These bacteria persist in the hemolymph of their adult host and exhibit efficient vertical transmission from mother to offspring. In this study, we analyzed the mechanism that underlies their vertical transmission, and here we provide strong evidence that these bacteria use the yolk uptake machinery to colonize the germ line. We show that Spiroplasma reaches the oocyte by passing through the intercellular space surrounding the ovarian follicle cells and is then endocytosed into oocytes within yolk granules during the vitellogenic stages of oogenesis. Mutations that disrupt yolk uptake by oocytes inhibit vertical Spiroplasma transmission and lead to an accumulation of these bacteria outside the oocyte. Impairment of yolk secretion by the fat body results in Spiroplasma not reaching the oocyte and a severe reduction of vertical transmission. We propose a model in which Spiroplasma first interacts with yolk in the hemolymph to gain access to the oocyte and then uses the yolk receptor, Yolkless, to be endocytosed into the oocyte. Cooption of the yolk uptake machinery is a powerful strategy for endosymbionts to target the germ line and achieve vertical transmission. This mechanism may apply to other endosymbionts and provides a possible explanation for endosymbiont host specificity.